Hitler Youth : growing up in Hitler's shadow - Bartoletti, Susan Campbell (New York : Scholastic, 2005)
A photo-illustrated look at the youth organizations Adolf Hitler founded and used to meet his sociopolitical and military ends; includes profiles of individual Hitler Youth members as well as young people who opposed the Nazis, such as Hans and Sophie Scholl.
Includes bibliographical references (p. 169-173) and index.
Wilson's Junior High School, November 2005
School Library Journal starred, June 2005
Book Links (A.L.A.), September 2005
Booklist starred, April 2005
Horn Book Starred, May 2005
Keywords: Hitler Youth; National socialism; Youth -- Germany -- History; Holocaust, 1933-1945.; Jewish children in the Holocaust